Age disparities in survival from lymphoma and myeloma: a comparison between US and England. (29th March 2014) - Pulte, Dianne; Redaniel, Maria T.; Lowry, Lisa; Bird, Jenny; Jeffreys, Mona
Summary Population‐level survival in older patients with lymphoma is significantly lower than in younger patients. In this study, data were obtained from cancer registries in England and the United States (US) for patients diagnosed with Hodgkin lymphoma (HL), non‐Hodgkin lymphoma (NHL) and myeloma. Five‐year relative survival was calculated using period analysis. Generalised linear models were used to determine excess hazard ratios (EHR) for older compared to younger patients. Five‐year relative survival was lower for older patients diagnosed with HL, NHL and myeloma in both countries. The greatest age‐related survival inequality was observed for patients with HL: in 2006–10 the EHR comparing patients aged 75 + years with those aged 15–24 years was 14·02 in the US and 15·69 in England. For NHL, the EHR was 1·91 in the US and 3·81 in England. For myeloma, comparing patients aged 75 + years with those aged 25–44 years, the EHR was 2·79 in the US and 3·60 in England. Survival of patients with lymphoma is lower for older patients in both the US and England but the discrepancy is less in the US. Physicians should be encouraged to evaluate patients' frailty and co‐morbidities as well as their age when considering treatment options for patients with lymphoma and myeloma.